The role of platform margin collapses and slope landslides in the initiation and evolution of submarine canyons - Chen, Junjin; Li, Qi; Wu, Shiguo; Liu, Shiqiao (Frontiers in Marine Science, 2024)
The Zhongsha Platform is the largest modern isolated carbonate platform of around 8600 km2 in the South China Sea, providing a unique case study for sedimentary processes in pure carbonate settings. High-resolution multibeam bathymetric data, two-dimensional seismic profiles, and surface sediment cores are utilizes to reveal the initiation and evolution of submarine canyons on the northeastern slope of the Zhongsha Platform. Three submarine canyons are revealed within the survey area that incise the slope at water depths between 600 and 4100 m. C1 presents a linear pattern, whereas C2 and C3 exhibit dendritic morphologies. A large-scale scalloped collapse has deeply excavated the platform margin and slope. Within this catastrophic failure, C2 originated in a northeastward orientation and subsequently converted to an eastward direction with a length of 54.8 km. It is distinguished by the erosion of numerous tributaries in the upper course, the transition of flow direction in the middle course, and the presence of retrogressive landslides in the lower course. Slope landslides extend eastward from middle-lower slope towards the oceanic basin at water depths ranging from 2300 to 4200 m. A series of scarps and immature canyons have developed with escarpments showing pronounced relief at the landslide heads. The triggering mechanisms of platform margin collapses and slope landslides are attributed to sediment aggradation, slope oversteepening, gravity flows, relative sea-level changes, surface monsoon currents, and deep cyclonic circulation. The canyon evolution is explained through four stages: Inception stage, sediment instability on platform margin and slope-toe; Expansion stage, the presence of platform margin collapses and slope landslides; Development stage, the initiation of submarine canyons eroded by gravity flows with downslope and retrogressive erosion; Present stage, the upper slope canyon incised into the landslide area and ultimately integrated with the lower slope canyon, creating an elongated modern canyon. This work contributes to enhance our understanding of the detailed morphology, transport processes, and triggering mechanisms of submarine canyons in the pure carbonate systems.